A Methodological Analysis of Articles Published in Malaysian Journals of Education - Sahari, Mohamad (Intellectual discourse, 1998)
The purpose of the study was to survey the research techniques reported in articles published in Malaysian educational journals, and to identify the standards that are deemed acceptable by these journals for assessing the adequacy of empirical research methods used in the articles. The study also explored differences between Malaysian journals and two prominent international journals in education with respect to the standards they adhered to when documenting methodological variables. To attain these objectives, all articles published between 1991 and 1997 in selected Malaysian journals were content-analyzed and compared to those published in the highly respected international journals from 1995 onwards. For each article, variables pertinent to research design and methods, sources of data, data collection procedure, and statistical analysis were coded using a structured checklist. Results were consistent with those of other studies in that: (i) there were a substantial number of studies using qualitative techniques, and more studies were qualitative than quantitative in nature, (ii) the most commonly used inferential techniques in the Malaysian journals were the ANOVA-based procedures, and (iii) the standards for documenting methodological adequacy deemed acceptable by the Malaysian journals did not exactly reflect the state of the art.